2010
DOI: 10.1016/s0034-7094(10)70062-3
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Transesophageal Echocardiography During Severe Hypotension in Non-cardiac Surgery

Abstract: Perioperative TEE was performed quickly, proving to be a useful technique in the context of hypotension during non-cardiac surgery. The heart and great vessels could be observed directly and functionally evaluated. Thus, the etiology of severe hypotension could be easily determined and managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20] All the studies were reported as comprehensive examinations, which was reflected in the broad diversity of diagnoses. As described previously, preoperative exams occurred immediately prior to induction of anesthesia and data from pre-assessment clinic exams were not included.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] All the studies were reported as comprehensive examinations, which was reflected in the broad diversity of diagnoses. As described previously, preoperative exams occurred immediately prior to induction of anesthesia and data from pre-assessment clinic exams were not included.…”
Section: Resultsmentioning
confidence: 99%
“…Recent paper published by Schulmeyer et al . demonstrated that TOE performed by trained anaesthetist during non-cardiac surgeries helped to establish cause of refractory hypotension in all 42 cases ( 3 ) . The most common cause of hypotension unresponsive to standard fluid bolus and ephedrine according to TOE findings were severe hypovolaemia (42%), followed by thromboembolic events (14%).…”
Section: Discussionmentioning
confidence: 99%
“…The second group consists of patients who are suffering unexplained hypotension or cardiac collapse in the perioperative setting, and ultrasound is used after the event to help diagnosis the cause of the hemodynamic instability. 1,2 A recent review by Jasudavisius et al looked at the use of either screening or rescue ultrasound with the intent of identifying common diagnoses to better inform teaching paradigms. 3 The Jasudavisius review identified 14 studies (nine transesophageal, four transthoracic, and one combined) that reported common findings in both the screening and rescue settings.…”
Section: Heartmentioning
confidence: 99%
“…Studies in patients requiring intraoperative echocardiography for hemodynamic collapse all suggested that this approach provided useful information to help guide the care of the patient. 1,2,12,13 Cardiac echocardiography in patients who clinically warrant an examination appears to have an important impact on patient care, although it is important to acknowledge that there are no large pragmatic trials to evaluate whether the change in management leads to improved outcomes and which patient populations may benefit the most. As skill levels increase, there is likely to be an increase in the use of ultrasound by non-cardiac anesthesiologists to either assess patients at high-risk of intraoperative events or to help guide the therapy of patients who have suffered either severe hemodynamic disturbances or cardiac arrest.…”
Section: Heartmentioning
confidence: 99%